1984
DOI: 10.1007/bf00146924
|View full text |Cite
|
Sign up to set email alerts
|

Defining risk

Abstract: Risk is the focal topic in the management of many activities and technologies. For that management to be successful, an explicit and accepted definition of the term "risk" is essential. Creation of that definition is a political act, expressing the definers' values regarding the relative importance of different possible adverse consequences for a particular decision. Those values, and with them the definition of risk, can change with changes in the decisionmaker, the technologies considered, or the decision pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
152
0
16

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 360 publications
(170 citation statements)
references
References 23 publications
(16 reference statements)
2
152
0
16
Order By: Relevance
“…[14] demonstrated that Project stakeholders tend to overemphasize the ‗consequence' aspect of risk leaving aside the ‗probability' dimension. This result was consistent with a research by [23] which identified that risk is more about the consequence than the unpredictability of the outcomes. [14] found that Project stakeholders in defining risk tend to over-focus on the negative sides while the rational decision theory would suggest a more neutral view.…”
Section: Project Program and Portfolio Risk Perceptionssupporting
confidence: 92%
“…[14] demonstrated that Project stakeholders tend to overemphasize the ‗consequence' aspect of risk leaving aside the ‗probability' dimension. This result was consistent with a research by [23] which identified that risk is more about the consequence than the unpredictability of the outcomes. [14] found that Project stakeholders in defining risk tend to over-focus on the negative sides while the rational decision theory would suggest a more neutral view.…”
Section: Project Program and Portfolio Risk Perceptionssupporting
confidence: 92%
“…Travel risk is defined as the possibility of experiencing a danger while engaging in travel (Fischhoff et al 1984) or the consciousness of security and knowledge of the likelihood of damage during travel (Wogalter et al 1999). Travel risk is perceived and experienced by tourists during the process of purchasing and consuming travel services (Tsaur et al 1997).…”
Section: Travel Riskmentioning
confidence: 99%
“…To measure quantitatively how risky something is, it is necessary to identify its adverse effects on those things that individuals consider to be valuable . But science provides no special insights into what society should value (Fischhoff, Watson, & Hope, 1984).…”
Section: Why Quantitative Risk Assessments Are Not Enoughmentioning
confidence: 99%